2002
DOI: 10.4049/jimmunol.168.6.2667
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Qualitatively Distinct MHC Class I-Restricted Presentation of Antigen Targeted to the Endoplasmic Reticulum

Abstract: For most nascent glycoprotein Ags, the MHC class I-restricted processing pathway begins in the endoplasmic reticulum (ER). From this location, they are translocated to the cytosol for degradation by the proteasome. A reasonable assumption is that processing of exocytic Ags is less efficient than that of cytosolic Ags, due to the requirement for additional handling, but that the processing pathways for the two types of proteins are otherwise similar. To test this, we compared the presentation of three epitopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Processing and presentation of NP 50 -57 to CTL is diminished in the presence of the proteasome inhibitor Lac (Fig. 1A), especially when Ag expression is limited (15). In contrast, generation of NP 147-155 from a full-length Ag is increased under similar conditions (Fig.…”
Section: Proteasome Inhibitor Sensitivity Of Np Epitopesmentioning
confidence: 81%
See 3 more Smart Citations
“…Processing and presentation of NP 50 -57 to CTL is diminished in the presence of the proteasome inhibitor Lac (Fig. 1A), especially when Ag expression is limited (15). In contrast, generation of NP 147-155 from a full-length Ag is increased under similar conditions (Fig.…”
Section: Proteasome Inhibitor Sensitivity Of Np Epitopesmentioning
confidence: 81%
“…We have observed previously that two MHC I-restricted epitopes of influenza A PR/8/34 NP exhibit opposite sensitivities to protease inhibitors that affect the proteasome (14,15). Processing and presentation of NP 50 -57 to CTL is diminished in the presence of the proteasome inhibitor Lac (Fig.…”
Section: Proteasome Inhibitor Sensitivity Of Np Epitopesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ER processing has been reported for the envelope protein of the human immunodeficiency virus 1 [41] and leader sequence-competent synthetic minigenes [42]. A recent study on the influenza virus NP showed that delivery of antigen to the ER yields efficient presentation [43]. Taken together, it is possible that in our case the NP 366-374 is also processed in the lumen of the ER in B lymphocytes and this may provide a selective advantage to the generation of a dominant CTL response.…”
Section: Discussionmentioning
confidence: 99%